2021
DOI: 10.1021/acs.orglett.1c01248
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Revision of Glyphaeaside C

Abstract: The iminosugar core of natural glyphaeaside C, originally assigned as a derivative of the piperidine natural product 1-deoxynojirimycin (DNJ), has been revised as a derivative of 2,5-dideoxy-2,5-imino-l-mannitol (l-DMDP) by the total synthesis of its enantiomer. This revised l-DMDP-derived configuration is the first of its kind to be observed in nature. The prepared iminosugars displayed the nanomolar inhibition of bovine liver β-glucosidase and β-galactosidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Through total synthesis of its antipode we revised its structure to a derivative of 2,5-dideoxy-2,5imino-L-mannitol. [72] This revised L-DMDP-derived configuration is the first of its kind to be observed in Nature. The synthesis involved ring opening of the novel epoxide 113 with a Gilman-like diorganocopper reagent to give the alcohol 114 which upon a cross-metathesis reaction with 115 gave 116 as a 4.8:1 mixture of E and Z isomers, respectively.…”
Section: Synthesis and Structural Correction To Glyphaeaside Cmentioning
confidence: 78%
“…Through total synthesis of its antipode we revised its structure to a derivative of 2,5-dideoxy-2,5imino-L-mannitol. [72] This revised L-DMDP-derived configuration is the first of its kind to be observed in Nature. The synthesis involved ring opening of the novel epoxide 113 with a Gilman-like diorganocopper reagent to give the alcohol 114 which upon a cross-metathesis reaction with 115 gave 116 as a 4.8:1 mixture of E and Z isomers, respectively.…”
Section: Synthesis and Structural Correction To Glyphaeaside Cmentioning
confidence: 78%
“…As electron-rich tertiary amines are known to suppress olefin metathesis reactions via coordination to ruthenium catalysts, the N -PMB group of 18 was oxidatively cleaved with CAN, and the resulting secondary amine was protected as N -Cbz carbamate 20 (Scheme ). Cross-metathesis of 20 with estragole derivative 21 using Grubbs’ first-generation catalyst afforded 1,2-disubstituted alkene 23 as an inseparable mixture of isomers ( E / Z ratio up to 4.6:1, combined yield up to 74%) . Hydrogenolysis/hydrogenation of E / Z - 23 over PdCl 2 afforded compound 24 as a trifluoroacetate salt after semipreparative RP-HPLC purification using a TFA-buffered solvent system in 16% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Method A: Compounds 20 (50 mg, 0.0651 mmol) and 21 (43.8 mg, 0.195 mmol) were co-evaporated with DCE (3 × 1 mL) and dissolved in anhydrous CH 2 Cl 2 (1.0 mL). The solution was degassed by sonication under argon flow for 10 min, followed by the addition of Grubbs’ first-generation catalyst (13.4 mg, 0.0163 mmol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the total synthesis of glyphaeaside C revealed that its structure closely resembles that of 2,5-dideoxy-2,5-imino-D-mannitol (D-DMDP). In 2021, Byatt et al [ 38 ] reported the multi-step facile synthesis of glyphaeaside C. The total synthesis of our target molecule initiated with the synthesis of pyrrolidine fragments from readily available starting reagent, i.e., 2,3,5-tri-O-benzyl-β-D-arabinofuranose 26 . The fragments were then reacted to give oxazolidinone a and b.…”
Section: Review Of the Literaturementioning
confidence: 99%